1,3-Bis(prop-2-ynyl)-1H-1,3-benzimidazol-2(3H)-one - Ouzidan, Younes (International Union of Crystallography, 2011)
In the title compound, C(13)H(10)N(2)O, the fused-ring system is essentially planar, the largest deviation from the mean plane being 0.015 (1) Å. The two propynyl groups are nearly perpendicular to the benzimidazole plane, making dihedral angles of 85 (3) and 80 (2) °, and point in opposite directions. There are two short intermolecular C—H⋯O contacts to the carbonyl O atom, one involving the acetylenic H atom and the other a H atom of the methylene group.